Marathon man [videorecording (DVD)] - Schlesinger, John, 1926-2003; Hoffman, Dustin, 1937-; Olivier, Laurence, 1907-1989; Scheider, Roy; Goldman, William, 1931-2018 (Paramount, 2017)
A Columbia graduate student becomes caught in a conspiracy surrounding a murderous Nazi fugitive.